2019
DOI: 10.1111/tri.13426
|View full text |Cite
|
Sign up to set email alerts
|

A novel concept for evaluation of pulmonary function utilizing PaO2/FiO2 difference at the distinctive FiO2 in cellularex vivolung perfusion—an experimental study

Abstract: For more accurate lung evaluation in ex vivo lung perfusion (EVLP), we have devised a new parameter, PaO 2 /FiO 2 ratio difference (PFD); PFD 1-0.4 = P/F ratio at FiO 2 1.0 -P/F ratio at FiO 2 0.4. The aim of this study is to compare PFD and transplant suitability, and physiological parameters utilized in cellular EVLP. Thirty-nine human donor lungs were perfused. At 2 h of EVLP, PFD 1-0.4 was compared with transplant suitability and physiological parameters. In a second study, 10 pig lungs were perfused in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This difference might explain the difference of inflammatory tissue cytokine levels. The favorable results of these series of prone EVLPs we reported, 13 suggested that some benefits of prone positioning in the clinical setting might in part translate to lung performance during EVLP along with other promising therapies to prevent IRI in EVLP; anti‐inflammatory drugs, 14,15 immunosuppressive drugs, 16,17 technical EVLP amendments, 18 and stem cell‐based approaches 19,20 …”
Section: Discussionmentioning
confidence: 96%
“…This difference might explain the difference of inflammatory tissue cytokine levels. The favorable results of these series of prone EVLPs we reported, 13 suggested that some benefits of prone positioning in the clinical setting might in part translate to lung performance during EVLP along with other promising therapies to prevent IRI in EVLP; anti‐inflammatory drugs, 14,15 immunosuppressive drugs, 16,17 technical EVLP amendments, 18 and stem cell‐based approaches 19,20 …”
Section: Discussionmentioning
confidence: 96%
“…Research initially focused on establishing optimal perfusion protocols, parameters for functional lung assessment, and, in clinical studies, their impact on, or correlation with, patient outcomes [ 2 , 3 ]. Recent studies have proposed more accurate methods of assessment, including the CLUE score [ 10 ] and the “PaO 2 /FiO 2 ratio difference” (the difference between PaO 2 /FiO 2 at a FiO 2 of 1.0 and 0.4) [ 11 ]. Lately, research has shifted focus to more sophisticated biomarkers and to assessing the efficacy of interventions on lung function or in reducing risks after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiology responsible for this improvement in function is still unclear. 42,43 The efficacy of mobile EVLP is currently being evaluated. The initial experience of using the OCS had been reported by the Hanover and Madrid groups.…”
Section: Clinical Outcomesmentioning
confidence: 99%